(untitled) (Research, Society and Development, 2022)
The entrepreneurial ecosystem is formed by a set of local attributes that together interrelate and contribute to the process of creating companies. These attributes are classified as cultural, social and material. Thus, this article’s main objective was to analyze the contributing attributes of local entrepreneurship, from the perspective of microentrepreneurs. The survey-type research method was used to build a quantitative approach to the problem. Data were obtained through the application of a questionnaire directed to microentrepreneurs. For data analysis, the technique called Confirmatory Factor Analysis with second-order indicator (a type of Structural Equation Modeling) was adopted. As a result, the determining attributes of local entrepreneurship, from the perspective of microentrepreneurs, are respectively: social, cultural and material. Thus, it is considered that social attributes are the main ones in the local ecosystem from the perspective of microentrepreneurs. The results presented in this study can serve as a basis for the development of public policies in order to encourage the creation and development of new companies in the researched location.